CFD Analysis Of Wind Turbine For 10 MW Electrical Power Generator In East Nusa Tenggara - Sutisna, Nanang Ali (President University, 2023)
Electrical energy has a vital role in daily human activities. The energy sources currently used in a generation are non-renewable energy sources. Wind energy is a renewable energy source that can be utilized as mechanical or electrical energy through a conversion called the Wind Energy Conversion System. In wind power plants, a somewhat important component is a wind turbine; the wind will drive the turbine and generate electricity from the generator. This study analyzed the suitability of turbine designs to be applied to wind power plants in East Nusa Tenggara, especially in three areas with a reasonably high wind potential compared to the surrounding area. Selection of appropriate wind turbine for electrical power generation in East Nusa Tenggara is the first phase of the study, it compared two wind turbine designs, namely Horizontal Axis Wind Turbine (HAWT) and Vertical Axis Wind Turbine (VAWT). Followed by analyzing the performance of the selected turbine using secondary data and analysis software, namely Ansys, to determine the torque generated by the wind turbine under study. The simulation results showed that the Horizontal Axis Wind Turbine produced power of 259.491 kW at a wind speed of 5.86 m/s and 271.447 kW at a wind speed of 6.13 m/s. Based on the results, the Horizontal Axis Wind Turbine needed for generating 10 MW is 56 units.